Local Wisdom and Islamic Character Development: The Educational Philosophy of Rumah Gadang - Yusutria; Charles; Rina Febriana (IBDA` : Jurnal Kajian Islam dan Budaya, 2026)
Character education has become a strategic issue in Indonesian education amid rapid globalization and digitalization, which have weakened moral values, social solidarity, and cultural identity among the younger generation. Local wisdom serves as a relevant and contextual source for strengthening national character. This study examines the Minangkabau community’s understanding of the philosophy of Rumah Gadang, identifies its embedded philosophical values, and analyzes the process of internalizing these values in the social, educational, and cultural lives of young people. Using a qualitative ethnographic interpretive approach, data were collected through in-depth interviews, participatory observation, and documentation involving Ninik Mamak, Bundo Kanduang, community leaders, educators, and Minangkabau youth. The findings reveal that the philosophy of Rumah Gadang remains part of the community’s collective consciousness, though its meaning and function have shifted with modernization. Values such as togetherness, deliberation, religiosity, responsibility, and cultural identity remain relevant, underscoring the need to revitalize Rumah Gadang's educational role through synergy among families, customary institutions, schools, and digital media.